HUBUNGAN ANTARA INTENSITAS BERMAIN GAME MOBILE LEGEND DAN PENGAWASAN ORANG TUA DENGAN PERILAKU AGRESIF VERBAL PADA ANAK REMAJA - Wibisono, Andika; Naryoso, Agus (Interaksi Online, 2019)
The development of technology is growing rapidly, especially in online video games and has an impact on the players, especially in adolescents. With the supervision of parents, it becomes the basis for reducing negative impacts such as aggressive created by violent video games. The purpose of this study was to determine the relationship between the intensity of playing mobile legend and parental supervision with verbal aggressive behavior in adolescents. In determining the hypothesis to be used, this study uses the theory of General Aggression model (GAM) and parental mediation with the Interaction Restrictions model. The study population was teenagers aged 16-18 years in the city of Semarang who played the Mobile Legend game. Based on the results of hypothesis testing carried out using Kendall's Tau b, the results show that: the significance value and correlation (H1) generated from Kendall's Tau b test results using SPSS obtained a significance value of 0.001 (where the significance level is smaller than 0.01 (≤ 1 %)) and the correlation coefficient value is 0.771 which shows that the relationship between variables has a positive correlation, and the level of the relationship is proven to be positively strong. Thus indicating that these results can be concluded. While the significance value and correlation (H2) generated from the results of testing Kendall's Tau b using SPSS obtained a significance value of 0,000 (where the significance level is smaller than 0.01 (≤ 1%)) and the correlation coefficient value is 0.782 which indicates that the relationship between variables have a positive correlation, and the level of the relationship is positive and strong. Thus indicating that these results can be concluded.